Analisis Penyerapan Anggaran Serta Implikasinya Terhadap Kinerja Manajerial : Studi Kasus Pada Pusat Penelitian Teh dan Kina Gambung Kabupaten Bandung Jawa Barat Lingkup Bagian Usaha - Amry, Syamsul; Sidqi, Abdul Gani; Fitriana, Fitriana; Yuliaty, Farida; Dongoran, Haddan (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study examines budget absorption and its implications for managerial performance, focusing on the case of the Tea and Cinchona Research Center (PPTK) Gambung, Bandung Regency, West Java. The research was motivated by the issue of low budget absorption at PPTK, which has impacted operational efficiency and managerial performance outcomes. The independent variables analyzed include sales volume, labor, and raw material costs. Budget absorption is an intervening variable, while managerial performance is the dependent variable. The study employed a quantitative method with descriptive and verificative approaches. Primary data were collected through questionnaires distributed to PPTK managers, and secondary data were obtained from financial and budget reports from 2018 to 2022. Statistical analysis was applied to assess the relationships among the variables. The findings reveal that sales volume, labor, and raw material costs significantly influence budget absorption. Additionally, effective budget absorption positively affects managerial performance. However, challenges such as declining budget absorption percentages and sales volumes in the last two years were identified, indicating room for improvement in budget management. This research recommends adopting more realistic and efficient budget planning, optimizing production processes, and enhancing monitoring mechanisms to improve budget utilization. These measures are expected to strengthen managerial performance and support the organization’s sustainability.